A study on the properties of zinc-enriched spent brewer’s yeast hydrolysate (Bulletin of the Institute of Chemistry and Chemical Technology, 2023)
The purpose of this study was to determine the physicochemical properties of the complex obtained by reacting spent brewer's yeast hydrolysate with zinc sulfate and to establish the possibility of its use. The zinc-enriched yeast hydrolysate was determined to contain 8.2% of total nitrogen, 2.72% of amino nitrogen, 0.5% of fat, 9.8% of ash, 5.4% of moisture, and 610 mg/kg of zinc. Peptide molecular mass distribution in zinc-enriched yeast hydrolysate was assessed using gel filtration chromatography, which gave results of >13.2 kDa - 3.2%, 1.54-13.2 kDa -75.5%, 13.2 кДa - 3.2%, 1.54-13.2 кДa - 75.5%,